Modeling the Impact of Ecological Restoration on Waterbird Diversity and Habitat Quality in Myanmar’s Moe Yun Gyi Wetland - Phyoe Marnn; Haider Ali; Haibo Jiang; Yang Liu; Ziqi Li; Sarfraz Ahmed; Tao Yang; Ziwei Li; Chunguang He (Biology)
The Moe Yun Gyi constructed wetland in Myanmar, located along the East Asian–Australian bird migration path, serves as a crucial habitat for migrating waterbirds. Protecting this biodiverse habitat is crucial in the face of ongoing threats, highlighting the need for effective conservation strategies. This study aims to evaluate the effects of the restoration on the populations of waterbirds from January 2014 to January 2024, by analyzing the composition and the spatiotemporal dynamics of waterbirds communities, with particular reference to changes in diversity. We measured waterbird quantity and species richness using the point count method, employing the Shannon-Wiener and DG–F Index formulae for diversity analysis. Habitat analysis was conducted with ArcGIS 10.6 and eCognition 10.3, while data analysis utilized RStudio and Microsoft Excel. The results indicate that restoration efforts in 2016 initially led to a decline in waterbird populations. Restoration efforts after 2017 resulted in a twofold increase in both diversity and abundance. However, in 2023, flooding in Bago City caused a decline in waterbird populations, impacting habitat rehabilitation. There was a notable rise in uncommon waterbird populations, especially threatened Pelecaniformes. The community’s richness has partially recovered, but seasonal water level volatility continues to impact diversity. The application of restoration techniques directly alters the extent and depth of water bodies, which are essential parameters for supporting appropriate waterbird habitats. We propose implementing a rational system for managing water levels, optimizing wetland hydrology, and enhancing water level regulation to safeguard significant resting areas along migration paths.